New Amperometric Methods for the Trace Determination of Pd(II) and Pt(IV) - Langyan, Ritu; Khatkar, S.P. (Asian Journal of Chemistry, 2012)
Amperometric determination of Pd(II) and Pt(IV) was successfully carried out with the help of thioglycolic acid at dropping mercury electrode (d.m.e.). 0.1 M NH3 + 0.1 M NH4Cl medium has been employed for Pd(II) and acetate buffer of pH 4.99 medium for Pt(IV). Both cathodic and anodic titrations were carried out successfully for Pd(II) in respective medium. Only cathodic titrations were carried out in case of Pt(IV). Metal species-TGA stoichiometry obtained was 1:2 for both the metal ions in respective mediums. Solutions as dilute as 1.06 ppm (Pd) and 9.75 ppm (Pt) were estimated in case of cathodic titrations and 10.64 ppm (Pd) was estimated in case of anodic titrations with high degree of accuracy. Tolerance limit for foreign ions has also been worked out.